State-of-the-Art and Future Directions in Structural Proteomics - Happonen, Lotta J; Varjosalo, Markku (Molecular and Cellular Proteomics, 2025)
Structural proteomics has undergone a profound transformation, driven by the convergence of advanced experimental methodologies and computational innovations. Cutting-edge mass spectrometry (MS)-based approaches, including cross-linking MS (XL-MS), hydrogen-deuterium exchange MS (HDX-MS), and limited proteolysis MS (LiP-MS), now enable unprecedented insights into protein topology, conformational dynamics, and protein-protein interactions. These methods, complemented by affinity purification (AP), co-immunoprecipitation (co-IP), proximity labeling (PL), and spatial proteomics techniques, have expanded our ability to characterize the structural proteome at a systems-wide scale. Integration with electron cryo-microscopy (cryo-EM), cryo-electron tomography (cryo-ET), nuclear magnetic resonance (NMR) spectroscopy, X-ray crystallography, and small-angle X-ray/neutron scattering (SAXS/SANS) methods has further driven the field of integrative structural biology. These methods, in conjunction with AI-driven predictive models such as AlphaFold and RoseTTAFold, enable the high-resolution modeling of protein complexes and dynamic assemblies, bridging the gap between static structures and real-time conformational changes. This review explores the current state-of-the-art in structural proteomics, with a focus on methodological advances and the integration of XL-MS, HDX-MS, and LiP-MS with methods in structural biology. We further discuss application of structural proteomics in deciphering disease mechanisms, identifying therapeutic targets, and guiding drug discovery, with these techniques poised to revolutionize precision medicine. Future directions emphasize fully integrative, multimodal approaches that unify experimental and computational paradigms, fostering a holistic understanding of the human proteome.
Copyright © 2025 The Authors. Published by Elsevier Inc. All rights reserved.